Integrating Maqāṣid Al-Sharīʿah Into Islamic Fintech: An Ethical Framework For Sustainable Digital Finance in the Era Of Industry 4.0 - Andi Martina Kamaruddin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid expansion of financial technology (fintech) in the Fourth Industrial Revolution and Society 5.0 era has fundamentally reshaped the global financial ecosystem, including the Islamic finance sector. As digital innovation enhances inclusivity and efficiency, it also introduces ethical and legal challenges to Sharia compliance. This study explores the integration of maqāṣid al-sharīʿah—the higher objectives of Islamic law—into the development of Sharia-compliant fintech in Indonesia. Using a qualitative library-based approach, the paper analyzes classical and contemporary Islamic scholarship, regulatory frameworks of the Financial Services Authority (OJK) and the National Sharia Council (DSN-MUI), and current technological innovations such as artificial intelligence (AI), blockchain, and QRIS Syariah. The findings reveal that the five core objectives of maqāṣid—ḥifẓ al-dīn (protection of religion), ḥifẓ al-nafs (life), ḥifẓ al-ʿaql(intellect), ḥifẓ al-nasl (progeny), and ḥifẓ al-māl (wealth)—serve as a normative and ethical compass for shaping digital finance grounded in justice, transparency, and social welfare. The study proposes a conceptual framework linking Sharia principles, digital ethics, and technological innovation, ensuring that fintech not only advances economic efficiency but also embodies moral and spiritual well-being in line with maqāṣid al-sharīʿah.